MLVA25 and CRISPR Genotypes of Yersinia pestis Strains from the Caspian Sandy Plague Focus - P. A. Goryunova; G. A. Eroshenko; A. N. Balykova; A. V. Kovrizhnikov; K. S. Shevchenko; L. M. Kukleva; E. A. Naryshkina; N. S. Chervyakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2024)
The aim of the work was to study the genetic diversity and spatial-temporal structure of Yersinia pestis in the Caspian sandy plague focus using MLVA25 and CRISPR typing methods.Materials and methods. 98 Y. pestis strains isolated in the territory of the Caspian sandy plague focus in 1925–2015 were used in the study. Whole genome sequencing was performed on Ion GeneStudio S5 System (ThermoFisher Scientific) and MGI (DNBSEQ-G50RS) platforms. Fragment sequencing was conducted using “ABI PRISM 3500XL”. The search for VNTR and CRISPR loci with subsequent alignment of nucleotide sequences was carried out in the MEGA X program. The obtained sequences were entered into the created database in the Bionumerics v7.6 (Applied Maths) software. The phylogenetic tree was constructed using the UPGMA method.Results and discussion. According to the results of MLVA25 and CRISPR analysis, 98 Y. pestis strains are divided into 60 genotypes (CS1 – CS60). Variability by 23 VNTR loci has been discovered. 7 new CRISPR spacers are described: 5 in YPa and 2 in YPb (size 31–33 bp, GC composition 34–58 %). The described spacers are designated as a108, a109, a110, a111, a112, b53, b54. The interrelation of changes in the copy number of VNTR loci depending on the place and time of isolation of strains has been revealed. The data obtained can be used to carry out molecular-genetic certification of the territory of the Caspian sandy plague focus and to study the routes and patterns of evolution and spatiotemporal circulation of Y. pestis populations in the Caspian plague foci.